2011
DOI: 10.1111/j.2044-8279.2011.02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of low and high achievers in early mathematics

Abstract: Background. Longitudinal studies allow us to identify, which specific maths skills are weak in young children, and whether there is a continuing weakness in these areas throughout their school years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 22 publications
1
23
0
7
Order By: Relevance
“…They found that the observed associations can partly be explained by intelligence, socioeconomic status (SES), social network support and socio-affective functioning as well as socio-demographic characteristics (Bull, Espy, Wiebe, Sheffield, & Nelson, 2011;Clark et al, 2010;Monette, Bigras, & Guay, 2011;Navarro et al, 2012). Although there are few studies reporting significant effects of confounding variables, the above results underscore the need to examine them carefully.…”
Section: Introductionmentioning
confidence: 90%
“…They found that the observed associations can partly be explained by intelligence, socioeconomic status (SES), social network support and socio-affective functioning as well as socio-demographic characteristics (Bull, Espy, Wiebe, Sheffield, & Nelson, 2011;Clark et al, 2010;Monette, Bigras, & Guay, 2011;Navarro et al, 2012). Although there are few studies reporting significant effects of confounding variables, the above results underscore the need to examine them carefully.…”
Section: Introductionmentioning
confidence: 90%
“…La validez predictiva fue calculada mediante correlaciones de los diferentes subtests del ENT-R con las puntuaciones en matemáticas obtenidas por una submuestra pasado un curso académico completo desde que fue evaluado con el ENT-r, los resultados son altamente satisfactorios y nos confirman la capacidad predictiva de la prueba. Los resultados confirman el carác-ter evolutivo del constructo sentido numérico ya observado en otros trabajos previos (Navarro et al, 2012). La prueba nos permite conocer el NCM de un sujeto o un grupo a temprana edad, posibilitando estrategias de intervención a estas edades que reduzcan la prevalencia de las DAM en cursos superiores.…”
Section: Discussionunclassified
“…En este sentido la investigación se ha limitado a problemas de cál-culo simple, siendo escasos los estudios en otros tipos de DAM (Fuchs et al, 2005). Parece que las dificultades se van manteniendo año tras año (Navarro, Aguilar et al, 2012).…”
Section: Introductionunclassified
“…De manera análoga, otros estudios ponen de relieve la importancia de las relaciones entre la habilidad del ejecutivo central y el rendimiento aritmético, de modo que los niños que tienen menos disponibilidad de recursos de memoria tienen también un menor rendimiento en tareas de cálculo (Navarro, Aguilar, Marchena, Ruiz, Menacho, y Van Luit, 2011). Son muchas las explicaciones actuales sobre las diferencias individuales y de desarrollo, recogidas en la literatura y que subrayan el papel que juegan algunos procesos cognitivos a la hora de determinar la conducta inteligente compleja, y que algunos autores relacionan con las altas capacidades intelectuales (Colom y Flores-Mendoza, 2001;Kane y Engle, 2002;Badeley, 2003).…”
Section: Discussionunclassified